The Impact of The Application of Digital Literacy on Teacher Competency Development At State Elementary School 8 Metro - Saputri, Rima Yuni; Muhisom, Muhisom; Kusuma, Febra Anjar (University of Lampung, 2024)
The problem in this study was that educators need to be more competent in digital literacy and be maximal in implementing 21st century education. This study aims to analyze the urgency of digital literacy in the 21st century education era for the competence of educators at SD Negeri 8 Metro Timur. This research uses descriptive methods and qualitative research types. The data collection technique was carried out by purposive sampling through observation, interviews, and documentation.. The data sources were educators, school principals, and education staff. The results showed that educators' understanding of digital literacy and 21st century education is quite good, with a percentage of educators who understand as much as 72%, while those who do not understand are only 28%. Educators are still at a medium level regarding skills in using digital media in the learning process. There are supporting and inhibiting factors in the implementation of 21st century education, such as facilities, parent educators, and students. Literacy Digital plays an important role and is a component of literacy that must exist in schools because good mastery of digital literacy can improve the professional competence of educators.Keywords: 21st century education, digital literacy, educator competenceDoi: https://doi.org/10.23960/JIPS/v5i2.59-62